Co‐Design in the Adaptation of a Clinical Decision Support System to Aid Violence Risk Assessment and Management: A Case Study - Anttila, Minna J.; Ameel, Maria K.; Rautiainen, Tinja; Anttila, Jenni; Maguire, Tessa; Daffern, Michael; Lantta, Tella (Wiley-Blackwell, 2026)
Introduction
The electronic application of a clinical decision support system (CDSS) conjoining the Dynamic Appraisal of Situational Aggression and the Aggression Prevention Protocol has been shown to be effective in reducing coercion and workplace violence in forensic settings in Australia. However, there is currently a lack of knowledge on the successful implementation of CDSSs across different cultural environments.
Aim
To describe the use of co-design in the adaptation of a CDSS, the eDASA+APP-FI in Finland.
Method
This qualitative case study followed a co-design framework involving a variety of methods, including analysing project data, rapid ethnography, and analysing the notes from co-design workshops.
Results
The adaptation of the CDSS into the local context included changes to the training programme and in the frequency of use of the CDSS, as well as linguistic adjustment.
Discussion
The co-design framework was valuable in identifying adaptation needs and in providing a sense of ownership among staff and consumers.
Limitations
Co-design can be time-consuming in clinical environments.
Implications
The results emphasise the importance of co-design in the identification of adaptation needs as part of the implementation process of a CDSS.
Recommendations
Co-design can be used as a framework when aiming to create a feasible CDSS.